Statement of Peer Review - Pavan Hiremath; Suhas Kowshik; Ritesh Bhat; Rajiv Selvam; Nithesh Naik (Engineering Proceedings)
In submitting conference proceedings to Engineering Proceedings, the volume editors of the proceedings certify to the publisher that all papers published in this volume have been subjected to a peer-review process administered by the volume editors [...]